Vitamin D Induces Increased Systolic Arterial Pressure via Vascular Reactivity and Mechanical Properties - Santos, Priscila Portugal dos [UNESP]; Murino Rafacho, Bruna Paola [UNESP]; Goncalves, Andrea de Freitas [UNESP]; Jaldin, Rodrigo Gibin [UNESP]; Nascimento, Thiago Bruder do; Barbosa Silva, Marcondes Alves; Assis Cau, Stefany Bruno; Roscani, Meliza Goi [UNESP]; Gaiolla, Paula Schmidt Azevedo [UNESP]; Minicucci, Marcos Ferreira [UNESP]; Tostes, Rita de Cassia; Zornoff, Leonardo Antonio Mamede [UNESP]; et al. (Public Library Science, 2014)
Background/Aims: The aim of this study was to evaluate whether supplementation of high doses of cholecalciferol for two months in normotensive rats results in increased systolic arterial pressure and which are the mechanisms involved. Specifically, this study assesses the potential effect on cardiac output as well as the changes in aortic structure and functional properties.Methods: Male Wistar rats were divided into three groups: 1) Control group (C, n = 20), with no supplementation of vitamin D, 2) VD3 (n = 19), supplemented with 3,000 IU vitamin D/kg of chow; 3) VD10 (n = 21), supplemented with 10,000 IU vitamin D/kg of chow. After two months, echocardiographic analyses, measurements of systolic arterial pressure (SAP), vascular reactivity, reactive oxygen species (ROS) generation, mechanical properties, histological analysis and metalloproteinase-2 and -9 activity were performed.Results: SAP was higher in VD3 and VD10 than in C rats (p = 0.001). Echocardiographic variables were not different among groups. Responses to phenylephrine in endothelium-denuded aortas was higher in VD3 compared to the C group (p = 0.041). Vascular relaxation induced by acetylcholine (p = 0.023) and sodium nitroprusside (p = 0.005) was impaired in both supplemented groups compared to the C group and apocynin treatment reversed impaired vasodilation. Collagen volume fraction (<0.001) and MMP-2 activity (p = 0.025) was higher in VD10 group compared to the VD3 group. Elastin volume fraction was lower in VD10 than in C and yield point was lower in VD3 than in C.Conclusion: Our findings support the view that vitamin D supplementation increases arterial pressure in normotensive rats and this is associated with structural and functional vascular changes, modulated by NADPH oxidase, nitric oxide, and extracellular matrix components.